2019
DOI: 10.1063/1.5086269
|View full text |Cite
|
Sign up to set email alerts
|

Transient superdiffusion of polydisperse vacuoles in highly motile amoeboid cells

Abstract: We perform a detailed statistical analysis of diffusive trajectories of membrane-enclosed vesicles (vacuoles) in the supercrowded cytoplasm of living Acanthamoeba castellanii cells. From the vacuole traces recorded in the center-of-area frame of moving amoebae, we examine the statistics of the time-averaged mean-squared displacements of vacuoles, their generalized diffusion coefficients and anomalous scaling exponents, the ergodicity breaking parameter, the non-Gaussian features of displacement distributions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 109 publications
2
24
0
Order By: Relevance
“…At time scale 0.2 < t < 2 s, molecular motors make the growth of EMSD super-diffusive with the anomalous exponent α ∼ 1.26 ± 0.02 and the ensemble generalized diffusion coefficient D α ∼ 0.082 ± 0.002 µm 2 /s α . Similar behaviour was observed for the transport of micron-sized beads along microtubules [51] and endosomes filled with labeled nonviral DNA-containing polyplexes ranging from 100 to 200 nm in diameter [10] and for single cell trajectories [52]. At longer time scales (t > 2 s), the EMSD become sub-diffusive (Fig.…”
Section: B Experimental Endosomal Trajectories Display Ergodic But An...supporting
confidence: 73%
“…At time scale 0.2 < t < 2 s, molecular motors make the growth of EMSD super-diffusive with the anomalous exponent α ∼ 1.26 ± 0.02 and the ensemble generalized diffusion coefficient D α ∼ 0.082 ± 0.002 µm 2 /s α . Similar behaviour was observed for the transport of micron-sized beads along microtubules [51] and endosomes filled with labeled nonviral DNA-containing polyplexes ranging from 100 to 200 nm in diameter [10] and for single cell trajectories [52]. At longer time scales (t > 2 s), the EMSD become sub-diffusive (Fig.…”
Section: B Experimental Endosomal Trajectories Display Ergodic But An...supporting
confidence: 73%
“…Lastly, our methods must be applied to the recent study on the static detection of particle positions [18]. It is important to note that the particle size considered in our simulations was infi nitesimal.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent past, a number of experimental and theoretical studies have been carried out to investigate the dynamics of the self-propelled species in crowded and complex environments [17][18][19][20][21][22][23][24][25] . Recent experimental and theoretical studies reported enhanced rotation of a self-propelled Janus particle in polymer solution 6,22 .…”
Section: Introductionmentioning
confidence: 99%